2017
DOI: 10.1016/j.braindev.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolinemia as a clue in the diagnosis of a patient with psychiatric manifestations

Abstract: Lately, microdeletions of the 22q region, responsible for DiGeorge syndrome or velocardiofacial syndrome, have been increasingly related to neuropsychiatric disorders including schizophrenia and bipolar disorder. These manifestations seem to be related to certain genes located in the hemideleted region such as the proline dehydrogenase (PRODH) and the catechol-o-methyltransferase (COMT) genes.We describe a teenager who started his adolescent psychiatric care presenting cognitive impairment, irritable mood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Three studies identified PRODH mutations on the residual allele in 22q11DS patients (Tables 1-3; Afenjar et al, 2007;Duarte et al, 2017;Raux et al, 2007). Twenty-nine 22q11DS patients were hyperprolinemic and had a second (i.e., on the residual allele) mutation in PRODH.…”
Section: Studies Including Hyperprolinemia Cases In Patients With 22q11dsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies identified PRODH mutations on the residual allele in 22q11DS patients (Tables 1-3; Afenjar et al, 2007;Duarte et al, 2017;Raux et al, 2007). Twenty-nine 22q11DS patients were hyperprolinemic and had a second (i.e., on the residual allele) mutation in PRODH.…”
Section: Studies Including Hyperprolinemia Cases In Patients With 22q11dsmentioning
confidence: 99%
“…Twenty-nine 22q11DS patients were hyperprolinemic and had a second (i.e., on the residual allele) mutation in PRODH. Of these patients, 24 had a developmental delay and/or intellectual disability (proline 339-1,275 μmol/L) and IQ ranged between 44 and 70 (Table 5) (Afenjar et al, 2007;Duarte et al, 2017;Raux et al, 2007). Eleven patients had an additional psychosis spectrum disorder, including seven patients with schizophrenia, one patient with schizoaffective disorder, two patients with atypical psychosis and one with schizotypal personality disorder (Table 5) (Duarte et al, 2017;Raux et al, 2007).…”
Section: Studies Including Hyperprolinemia Cases In Patients With 22q11dsmentioning
confidence: 99%
“…On the other hand, the perturbed metabolism of l-Pro can result in hereditary disorders characterized by an excessive level of l-Pro in the blood, known as hyperprolinemia type I (due to the deficiency of the enzyme proline oxidase) or type II (due to its complete lack) [35,36]. Based on clinical results, certain researchers relate hyperprolinemia to schizophrenia [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The de ciency of the P5C and P5CD enzymes leads to hyperprolinemia type I and type II, respectively. PRODH is located in the 22q11 chromosomal region, where microdeletions, which are responsible for DiGeorge (velocardiofacial) syndrome, can present with psychiatric disorders [2]. Clinical ndings that develop due to HPI vary.…”
Section: Introductionmentioning
confidence: 99%